The Effect of Red Bean and Red Spinach Flour Substitution on the Organoleptic Properties and Nutritional Value of Fried Meatballs (Basreng) - Naiaki, Rosina Chasandra; Nur, Astuti; Hasan, Tobianus (Media Publikasi Cendekia Indonesia, 2024)
This study investigates the impact of substituting red bean flour and red spinach flour on the organoleptic properties and nutritional value of fried meatballs (Basreng). Three treatments were tested: P1 (5% red bean flour and 5% red spinach flour), P2 (10% red bean flour and 10% red spinach flour), and P3 (15% red bean flour and 15% red spinach flour). Fifty third-semester nutrition students evaluated taste, texture, aroma, and color using a 5-point hedonic scale. Statistical analysis included normality tests, ANOVA for normally distributed data, and Kruskal-Wallis tests for non-normally distributed data, followed by Duncan or Mann-Whitney tests for significant differences. Results indicated that P1 was most favored in all sensory aspects. Increasing concentrations of red bean and red spinach flours resulted in a stronger taste and aroma of these ingredients, which overshadowed the chicken flavor. P3, though less preferred organoleptically, provided the highest nutritional value with 0.06 mg of iron per slice. This study highlights the balance between sensory acceptance and nutritional enhancement using local ingredients. While P1 is optimal for consumer preference, P3 offers significant nutritional benefits. The findings suggest that red bean and red spinach flours have potential in improving the health benefits of traditional snacks like Basreng